(untitled) (Research, Society and Development, 2020)
Objective: to know the feelings of mothers about the illness of their child with leukemia. Method: descriptive research, with a qualitative approach, carried out between the months of October and November 2017, at the chemotherapy outpatient clinic of a reference hospital in pediatric oncology, in Ceará, Brazil. The study took place with 11 mothers, based on individual semi-structured changes, organized using Bardin’s content analysis technique. The theoretical basis consisted of Martin Heidegger’s phenomenological Hermeneutics. Results: the mothers’ reports were categorized into two topics: “The perception of the disease’s disclosure: the mother’s discovery of the diagnosis” and “The family after the discovery”. A difficulty was evidenced when they received the news about the diagnosis of a child with leukemia and the existence of a chronic disease. When talking about this subject, it was observed that deep changes in the independent emotional structure to flow causing expressions of sadness. Conclusion: it is perceived that the family dynamics undergoes processes of changes in their dimensions, and that from then on, relationships go through associations around seeking better commitment in the life of those who demand it. The mothers’ feelings and fears give another meaning in the search for care, as an instinct that is characteristic of living beings.